Comparative analysis of tangible and intangible factors in selecting the optimal location for a small-scale industry - Adekunle Ibrahim MUSA; Kapil CHAUDHARY; Daniel Jesuyon POHETO (Universitas Sultan Ageng Tirtayasa, 2026)
Selecting an optimal location is critical for the sustainability and competitiveness of small-scale industries. This study evaluates three Nigerian states Lagos, Ogun, and Oyo using a multi-criteria decision-making (MCDM) approach. A Simple Additive Weighting (SAW) model was applied to assess both tangible factors and intangible factors. Data were collected from 30 purposively selected respondents and secondary sources. Results indicated that Oyo State ranks highest (7.85), followed by Lagos and Ogun (7.64 each). The study concludes that Oyo is the best option for cost-conscious investors, Lagos suits businesses prioritizing infrastructure, while Ogun is viable for low-cost operations with manageable security risks. The robustness of the results was confirmed by a sensitivity analysis (70:30 weighting). The paper is significant as it incorporates tangible-intangible trade-offs in the location choices of SMEs in the framework of a developing economy. The findings emphasize a holistic approach to location selection. Future studies should explore technology and sustainability in industrial location decisions.